Adverse prognosis of incidentally detected ambulatory atrial fibrillation - Martinez, Carlos; Katholing, Anja; Freedman, Saul Benedict (Thrombosis and Haemostasis, 2014)
It was the aim of this study to determine prognosis of incidentally detected ambulatory atrial fibrillation (IA-AF) and its response to antithrombotic therapy. We performed a cohort study of 5,555 patients with IA-AF (mean age 70.9 ± 10.1, 38.4% female) and 24,705 age- and gender-matched controls without AF followed three years using UK Clinical Practice Research Datalink. We measured incidence rates of stroke, all-cause mortality, myocardial infarction, major bleeding, and effect of antithrombotic therapy. Patients with IA-AF had mean CHA2DS2VASc score 2.5 ± 1.5, 73% with score ≥2. The stroke incidence rate (IR) was 19.4 (95% confidence interval 17.1 – 21.9)/1,000 person-years vs 8.4 (7.7 – 9.1) in controls (p<0.001), mortality 40.1 (36.8 – 43.6)/1,000 person-years vs 20.9 (19.8 – 22.0) in controls (p<0.001), and myocardial infarction 9.0 (7.5 – 10.8)/1,000 person-years vs 6.5 (5.9 – 7.2) in controls (p<0.001). IRs of all endpoints increased with age. Oral anticoagulant ± antiplatelet therapy received by 51.0% in year following IA-AF was associated with adjusted hazard ratio (HR) of 0.35 (0.17 – 0.71) for stroke, and 0.56 (0.36 – 0.85) for death compared to no therapy, while antiplatelet treatment was associated with a non-significant reduction of HR: 0.81 (0.51 – 1.29) for stroke, and 0.80 (0.55 – 1.15) for death, though both carried a similar small non-significant adjusted excess IR of major bleeding. In conclusion, asymptomatic AF detected incidentally is associated with a significant adverse effect on stroke and death, with reduction in both associated with oral anticoagulant but not antiplatelet treatment. This provides justification to assess cost-effectiveness of community screening to detect unknown AF.